Evaluation of The Wastewater Treatment Plant (WWTP) Management System at the Ibnu Sina Islamic Hospital Padang - Yasril, Abdi Iswahyudi; Fitri Andria Sari; Frinaldi, Aldri; Rembrant, Rembrant; Apriliani, Cici; Febrina, Cory; Amelia, Kiki; Audia, Washila (Science and Environmental Journal for Postgraduate, 2025)
Managing hospital liquid waste is very important to prevent environmental pollution. Ibnu Sina Islamic Hospital in Padang, as a referral hospital, generates liquid waste that must be treated according to quality standards. This study aims to evaluate the management of liquid waste at RSI Ibnu Sina Padang in 2025, considering input, process, and output. The research method uses a descriptive qualitative approach or in-depth interviews thru interviews, observation, and document review with triangulation analysis. The number of informants to be studied is 6 people. The research results show that the inputs, including policies, human resources, budget, and infrastructure, are generally adequate. The planning process is carried out thru annual evaluations, implementation is based on SOPs, and routine monitoring is done with external laboratory tests. The output shows that most of the liquid waste parameters (BOD, COD, TSS, ammonia, oil and grease, pH) meet the quality standards, although fluctuations sometimes occur in pH and coliform. The main constraints are damage to the wastewater treatment plant equipment and delays in repairs due to funding/budget. It can be concluded that the management of liquid waste at RSI Ibnu Sina Padang has been quite effective, but continuous monitoring, the provision of backup equipment, and improved cross-sectoral coordination are still needed to optimally control environmental pollution.